Lirik Yaa Lal Wathon: Interpretasi Karya KH Wahab Hasbullah dalam Konstruksi Nasionalisme Siswa Sekolah Dasar: (Studi Pada Siswa SDN Aengtabar 1 Tanjungbumi Kabupaten Bangkalan) - Muhaimin Muhaimin (STAI Syaichona Moh. Cholil Bangkalan, 2021)
The nationalism educations to the generation become an important thing to do by the mount of departments, especially in Education. The nationalism strengthening in the basic construction of the elementary school students is effective to do through an interesting and fun teaching and learning prosess, such as songs and lyrics. This study aims to describe and analyze an interpretation and response to the students nationalism strengthening toward Yaa Lal Wathon lyric and song created by KH. Wahab Hasbullah. The research design is qualitative approach. The subjects are high grade students of SDN Aengtaber 1 Tanjungbumi Bangkalan by dokumentalisting the interpretation fortofolio of the Ya Lal Wathon lyric and interviewing about the natinalism. The data analysis is used as the analysis content from the student’s interpretation and response. The learning implementation using Ya Lal Wathon song by KH. Wahab Hasbullah is effective to improve the student’s self-awareness in the noble toward nationalism development. This lyric consists of the fatherland love education in which Muslim keep the country. Those are the reasons why we need an innovative learning approach and strategy either theory or practice in the learning which builts the nationalist.